Berbanjar.com: Open Educational Resources Use to Initialize Instructional Digitalization - Sutisna, M Ridwan (PEDAGOGIA, 2024)
This main objective of this study is to acknowledge the use of berbanjar.com as open educational resources and to seek its potential use by the prospective teacher. Using case study by capturing data of the website content for the last two years after launched in 2020. Interviewing ninety-four respondents of pre-service teacher user of berbanjar.com as prospective teacher regarding their ability to develop their instructional materials and their preference to use web-based open educational resourced such as berbanjar.com. The result of the study captures more than three thousand of teaching materials has been uploaded to berbanjar.com. Instructional video, editable PowerPoint presentations and infographics is by sequence the most numerous contents of berbanjar.com. More than fifty respondents confident about their ability to develop their own materials and have the willingness to share it to others by using berbanjar.com. The use of web-based open educational resources such as berbanjar.com can help teacher to deliver their instruction digitally. The high reception of berbanjar.com by its user, in this case indicate that open educational resources can help initiate the digitalization of education.